PROFIT EFFICIENCY AND DETERMINANTS OF PROFITABILITY IN VIETNAM BANKING FROM 2009-2014 - Tran, Lan Huong (2015)
Employing a translog profit function, we first estimate and compare profit efficiency of 44 commercial banks in Vietnam over the period 2009-2014. The efficiency scores are estimated by stochastic frontier approach (SFA) under the assumption that inefficiency term follows a truncated normal distribution with only positive values and is directly affected by environmental factors. Our results reveal a relatively high profit efficiency of 83% on average. Regarding types of ownership, Joint venture banks are more efficient than foreign-owned banks and state-owned banks, while private-owned banks are found to be the least efficient during the period. Profit efficiency estimation in the 1st stage is then included in the 2nd stage model as a suspected endogenous regressor. Together with efficiency variable, other bank-specific, industry-specific and macro-economic variables are also captured in the model to identify the driving factors of bank profitability. The endogeneity problem and dynamic nature of the profit model is addressed by using system generalised method of moments (SGMM). The regression results support the X-efficiency hypothesis that profit efficiency is positively correlated to bank profitability. However, they are not identical in explaining the relative ranking of bank performance. However, there is no evidence to support the structure conduct performance (SCP) hypothesis since concentration is found to have negative impact on bank profitability. Vietnam commercial banks appear to be highly sensitive with the changes in its operating environment. While the increase of money supply growth and inflation negatively affect the bank performance, the rise in GDP growth can lead to the improvement of the profit ratio.